O corpo e a técnica : a superação do humano na modernidade técnica? - Santos, Daniela Rodrigues dos (2011)
Within debates and disputes about the stature of the human and its importance within the technical development we face the multiplicity of approaches revealed. Contrary views beckon both the extinction of humanity, and to overcome them. The meaning attributed to men and their actions in pursuit of steady improvement of its biological apparatus imply specific understandings about society and about the technique, because it appears as a decisive force in the construction of new social paradigms. So we launched into the understanding of this scene in the modern technique, with special attention to the question about man and his supposed imminent end as a result of technological development seeking common links to competing perspectives, as well as their differences. We present an exploratory overview of opposing views on the technical implementation of human possibilities within the context of the sociological study of man and technology. In this sense, the post-humanism is a route of criticism and renewal of important concepts located within this issue.